Communication Accommodation Strategy Among Members of the OMORI Online Community: A Case Study on the Use of Semantic Shifted Slang by Generation Z - Yovan Immanuel; Jandy Edipson Luik; Lady Joanne Tjahyana (Scriptura, 2025)
Communication accommodation is a process that is undergone by all new members of a community. The rapid growth of online communities among Generation Z has fostered the emergence of unique linguistic practices, including semantic-shifted slang, which can present challenges for new members to adapt and integrate. This study examines how communication accommodation strategies are employed by members of the OMORI virtual community on Discord, focusing on the use of semantic-shifted slang as a tool for group adaptation. The OMORI community serves as a platform for the players to meet and discuss with other OMORI players. This study attempts to research the OMORI virtual community in Discord, where the group members also often have other smaller groups which help them in their communication accommodation process. Employing a case study qualitative approach through semi-structured interviews, findings reveal that convergence—through observation, imitation, and gradual adoption of slang—is the dominant strategy, with small groups serving as safe spaces for experimentation and learning. Divergence also occurs when slang conflicts with personal identity or self-image. This research contributes to the field of communication studies by deepening the understanding of Communication Accommodation Theory in virtual, interest-based communities, highlighting how slang functions as both a symbolic and practical tool for fostering cohesion, negotiating identity, and strengthening group membership in online spaces.